ATP-Driven Remodeling of the Linker Domain in the Dynein Motor - Roberts, Anthony J. (Cell Press, 2012)
Dynein ATPases are the largest known cytoskeletal motors and perform critical functions in cells: carrying cargo along microtubules in the cytoplasm and powering flagellar beating. Dyneins are members of the AAA+ superfamily of ring-shaped enzymes, but how they harness this architecture to produce movement is poorly understood. Here, we have used cryo-EM to determine 3D maps of native flagellar dynein-c and a cytoplasmic dynein motor domain in different nucleotide states. The structures show key sites of conformational change within the AAA+ ring and a large rearrangement of the “linker” domain, involving a hinge near its middle. Analysis of a mutant in which the linker “undocks” from the ring indicates that linker remodeling requires energy that is supplied by interactions with the AAA+ modules. Fitting the dynein-c structures into flagellar tomograms suggests how this mechanism could drive sliding between microtubules, and also has implications for cytoplasmic cargo transport.